Longitudinal association between addictive internet use and depression in early adolescents over a 2-year period: A study using a random intercept cross-lagged model. (July 2022) - Takahashi, Michio; Adachi, Masaki; Hirota, Tomoya; Nishimura, Tomoko; Shinkawa, Hiroki; Mori, Hiroyuki; Nakamura, Kazuhiko
Abstract: Although addictive internet use (AIU) and depression frequently co-occur in early adolescents, the mechanism accounting for their co-occurrence remains unclear. The aim of the present study was to clarify the longitudinal reciprocal relationships between AIU and depression in early adolescents. We employed a random intercept cross-lagged model to examine the longitudinal reciprocal relationships between AIU and depression in a sample of the early adolescent population comprising 1361 children (aged 12–13 at baseline) over the two-year study period. Our results revealed no significant longitudinal reciprocal relationship between AIU and depression, suggesting that AIU was neither the cause nor the result of depression in early adolescence. The random intercepts of AIU and depression were significantly correlated. Additionally, the concurrent relationships between these two conditions were significant at all time points. These results indicate that early adolescents with more severe AIU had more severe depression. We also demonstrate that the same reciprocal patterns of AIU and depression were observed in males and females. Therefore, our results suggest that, during the early adolescent period, AIU does not influence the severity of depression a year later and vice versa and that there are common causes for both conditions. Highlights: The co-occurrence mechanism of addictive internet use and depression remains unclear. We examined the longitudinal relationships between addictive internet use and depression. Our results showed no longitudinal relationships between addictive internet use and depression.